Antihyperlipidemic Property of a Dietary Supplement of Moringa Oleifera Leaves and Pleurotus Ostreatus in Wistar Rats Stressed by Combination of Ethanol-Paracetamol. (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: moringa oleifera; pleurotus ostreatus; dietary supplement; antihyperlipidemic; oxidative stress